ANALISA PERMASALAHAN DAN RENCANA PELEBARAN SALURAN DRAINASE DI DAERAH JALAN CIMAHPAR - Mutiasari Oktavia; Rulhendri Rulhendri (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2023)
Flood control buildings or commonly known as drainage channels are a global element of the legacy of infrastructure to help facilitate community activities and are a major component of road support construction. The Jalan Cimahpar area which is the main road that connects to Jalan Pandu Raya, an area where the majority of the people sell and pass through the road is still facing various problems. Problems that are quite disturbing to the community are when there is high rainfall, there is a puddle of water on the shoulders and road bodies as a result of overflowing drainage channels that are not functioning properly, as a result, the busyness of the community and road users falters. The slope of the road and the accumulated sediment is also one of the factors that causes the drainage water to not function properly. Thus, it is necessary to expand the drainage channel that is able to accommodate puddles of water during high rainfall.